Large Scale B2B via Web Services scaling mission critical web service for hundreds of partners. - Wessels, Allan (SOA webservices journal.)
Over the past few years Web services have grown from a conceptual draft based on the ideal of cross-platform programmatic interoperability to a formal specification and a vision of grand-scale distributed system architectures. Today we are putting that vision to work and designing systems with service-oriented architectures that are critical to our businesses. Amazon.com has been one of the forerunners in the adoption and promotion of Web services. Consistently striving to remain on the forefront of technology, Amazon has thoroughly embraced Web services so much so in fact, that you can tie some serious revenue numbers directly to the external use of Amazon's Web services. For the remainder of this article I will outline for you just one of the avenues Amazon has taken to leverage Web services to generate new business.